Corporate social responsibility and earnings management within the managerial psychological context. (2017) - Hamza, Sourour; Jarboui, Anis
Previous studies explain the association between corporate social responsibility and earnings management from the stakeholders', legitimacy, agency and singling theories. This research aims to explore this relation from psychological and behavioural theory perspective. We deal with the psychological characteristics of the manager such as the manager's reasoning, overconfidence and affects (shame and guilt). This article shows that the manager's psychology may influence significantly his attitude toward corporate social responsibility and earnings management. Accordingly, the psychological feature may explain and determine the relation between corporate social responsibility and earnings management.